Hubungan Panjang Puntung (STUMP) Indeks Massa Tubuh (IMT) Dengan Keseimbangan Berjalan Dan Kepercayaan Diri Pada Pasien Post Amputasi Anggota Gerak Bawah - Muhammad Syaifuddin; Bhisma Murti (Poltekkes Kemenkes Surakarta, 2016)
Abstract : Long Stump (Stump), IMT, Walking Balance, Self-Confidence. Amputation can be interpreted as an act of separating the body part or all extremities. Amputation in locomotor lower reaches 85-90 % of all amputations and below-knee amputation (transtibial amputation) is a type of amputation surgery is most often performed. The loss of the lower limbs resulting in disruption of limb function, with one of which is a function of balance and also one's confidence. The study was an observational analytic research with cross sectional design. Clinical research sites in Karanganyar Jaten Kuspito sample were patients with post- amputation of the lower limbs as many as 52 people with technique Comparative study of means. Data collection techniques using questionnaires and literature. Analysis of data using linear regression . There was a positive correlation was statistically significant between the length of the stump (b1 = 0.49 ; 95 % CI ; 0.15 to 0.84 ; p = 0.006) and IMT (b2 = 0.31 ; CI 95 % ; 0.09 to 0.53; p = 0.006) with the balance to walk, there was a positive correlation was statistically significant between the length of the stump (b1 = 1.37 ; CI 95 % ; 0,41 to 2.33 ; p = 0.006) and IMT (b2 = -0.76 ; 95 % CI ; -1.37 to -0.16 ; p = 0.015) with confidence. Long stump (stump) and body mass index (BMI) was associated with a walking balance and self confidence .